From extra to extraordinary: an academic and practical exploration of extraordinary (E) pro environmental behavior (PEB) in the hotel industry - Zizka, Laura; Dias, Álvaro; HO, Jo Ann; Simpson, Shaniel Bernard; Singal, Manisha (Elsevier, 2024)
Over the past decades, organizations have become increasingly involved with environmental concerns to mitigate the negative consequences of their actions on the community. The hospitality industry, and especially hotels, aware of its effects, has taken steps to increase positive environmental behavior, attitudes, and initiatives, to lessen the harm to the greater community in which they are located. Encouraging employees in their pro-environmental behavior (PEB) within the organization is a long-standing initiative and well-cited in the literature. In this paper, we posit the need to extend the literature to an “extraordinary” (E) version of PEB i.e. extraordinary pro-environmental behavior via employee engagement. Our study examines traditional PEB through a systematic literature review deriving from eleven top-ranked journals for 79 articles, identifying key concepts through Leximancer. In addition, two workshops with international hospitality professionals were held to complement findings from the literature. Our contribution lies in developing a model that academics and hotel stakeholders can use to move beyond PEB to our proposition of E-PEB as well as address the practitioner-academia gap by comparing what the literature posits with the reality of the hotel industry.